Visual analysis of literature in the association research field between CRISPR and food safety based on Web of Science database - QIN Shoucheng; SUN Xueyan; ZHAO Xihong (浙江大学学报. 农业与生命科学版, 2024)
In order to understand the development dynamics of CRISPR technology in the field of food safety, this study conducted a search in the Web of Science Core Collection using the keywords “CRISPR” and “Food safety or Food security”. A total of 415 relevant papers published between 2011 and 2023 were obtained. Using CiteSpace software, a comprehensive analysis was conducted on publication time, publication countries, publication institutions, source publications, keywords, and references of these papers. The results revealed that papers related to CRISPR and food safety research were predominantly concentrated from 2017 to 2022, with a continuous annual increase, and the fastest growth occurred from 2020 to 2022. China had the largest number of published papers. Three institutions had significant academic influence: the Chinese Academy of Agricultural Sciences, Zhejiang University, and Indian Council of Agricultural Research. The journal with the largest number of publications was Frontiers in Plant Science. Keywords such as gene editing, CRISPR-Cas9, resistance, interference, yield, mutagenesis, and endonuclease were identified as hotspots in this association field. Research on foodborne pathogen, abiotic stress, crop breeding, and disease resistance has emerged as a forefront area in this field. The application of CRISPR technology in the field of food safety has far-reaching implications for ensuring people’s physical health and enhancing agricultural production and will continue to hold significant development potential in the future.